Field-assisted exciton dissociation in highly efficient PffBT4T-2OD: Fullerene organic solar cells - Weu, Andreas; Lami, Vincent; Kreß, Joshua; Vaynzof, Yana (Chemistry of materials, 2018)
Understanding the photophysics of charge generation in organic semiconductors is a critical step toward the further optimization of organic solar cells. The separation of electron-hole pairs in systems with large energy offsets is relatively well-understood; however, the photophysics in blends with low driving energy remains unclear. Herein, we use the material system PffBT4T-2OD:PC71BM as an example to show that the built-in electric field plays a critical role toward long-range charge separation in high-performance devices. By using steady-state and time-resolved spectroscopic techniques, we show that in neat films an energetic barrier impedes polymer exciton dissociation, preventing charge transfer to the fullerene acceptor. In complete devices, this barrier is diminished due to the built-in electric field provided by the interlayers/contacts and accompanying space-charge distribution. The observed behavior could also be relevant to other systems with low driving energy and emphasizes the importance of using complete devices, rather than solely films, for photophysical studies.
Gesehen am 12.03.2020